The The Influence of Green Practices and Promotions on the Buying Interest of Café Consumers in Jakarta: the Role of Environmental Awareness as A Moderation Variable - Rachmanita, Sheila; Mulyowahyudi, Alugoro (Dinasti International Journal of Digital Business Management, 2025)
Sustainability in the business industry, including the café sector, is a major concern in efforts to reduce environmental impact. This study uses a quantitative method with data collection techniques through surveys distributed to café consumers in Jakarta.The data obtained is analyzed using  the Structural Equation Modeling (SEM)  method with the Partial Least Square (PLS) approach. These findings indicate that cafes that implement environmentally friendly practices as well as effective green promotion strategies can increase consumer buying interest, especially for those with a high level of environmental awareness. The implications of this study provide insights for café industry players to be more active in implementing sustainable business practices and communicating their environmental commitments to consumers.